The Potential of Earthworms (Eudrilus eugeniae) in Vermicompost Production from Vegetable Market of Waste Cabbage and Fruit Skins (Sainteknol : Jurnal Sains dan Teknologi, 2023)
Traditional markets are one of the highest contributors to waste. Traditional markets can produce a lot of waste, one of the wastes with a large amount is organic waste. The alternative that can be done to deal with organic waste and can be converted into a product is to make compost using the vermicompost method. The aim of this study was to find out the length of time for composting in the manufacture of compost, to determine the optimal amount of Eudrilus eugeniae in the composting process, and to find out the optimal distribution of waste in composting. The incubation process for compost was carried out for 8 weeks, with sampling at weeks 4, 6, and 8. Sampling was carried out to analyze the macronutrient content consisting of C-Organic, nitrogen, and potassium. Content analysis was carried out using UV/VIS spectrophotometry for analysis of C-Organic content, Kjeldahl method for nitrogen content analysis, and Atomic Absorption Spectrophotometer (AAS) for potassium content analysis. The specifications for compost from organic waste are based on the Indonesian National Standard (SNI 19-7030-2004). This research resulted in C-Organic content of 6.1-8.1%, nitrogen content of 0.32-0.43%, and potassium content of 0.16-0.23%.